Perbedaan Mekanisme Koping Antara Mahasiswa Laki-Laki dan Perempuan dalam Menghadapi Ujian Semester pada Fakultas Tarbiyah Iain Raden Intan Lampung. - Thahir, Andi (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2014)
Students in RI Government regulation No.30 of 1990 are registered learners and study in certain universities. Students are a group in a society that obtains its status because of ties with college. In male student variable, 160 respondents (64%) have constructive coping mechanism and 90 respondents (36%) have destructive coping mechanism. In the female variable, 200 respondents (80%) have constructive coping mechanism and 50 respondents (20%) have destructive coping mechanism. The result of Bivariate analysis using Chi Square obtained χ² count = 0,893 dan χ² table = 3,488. This means there is no difference in coping mechanism between male and female students in facing the odd semester exam of academic year 2010/2011 at Faculty of Tarbiyah IAIN Raden Intan Lampung.